INSTAGRAM AS A CYCLISTS’ EXISTENCY MEDIA DURING COVID-19 PANDEMIC - Ririn Puspita Tutiasari; Syafrida Nurrachmi Febriyanti; Ahmad Fahri Huzain; Abizard Sakti Nugroho (Universitas Islam Balitar, 2021)
Cycling in recent months has become a new trend, interestingly this trend occurs when the corona virus outbreak or what is often referred to as Covid-19 is hitting this country. At first people cycled on the grounds of increasing immunity or immunity, because during the Covid-19 pandemic the body had to be strong to fight the virus. To fight the virus, people are advised to stay at home and if they have to go outside, they must comply with health protocols, namely: wear a mask and keep your distance. During the Covid-19 pandemic cycling was the sport of choice for the people. Cycling is an activity that makes the body healthy, but during this period, it is very vulnerable to transmission of the corona virus when cycling and hanging out together. According to several reports, there are several new clusters of activities for cyclists. This cycling activity is very interesting and has a lot of followers, this can be seen from the many people who make statuses or post photos while cycling on their social media. The most widely used social media is Instagram, they post as status or as Instagram Stories. Many people post photos on Instagram as their existence to fill activities during the Covid-19 epidemic. Collecting data in this study by means of observation and in-depth interviews. The results of this research are, posting cycling photos is a form of existence during a pandemic, cyclists upload photos on Instagram as a form of education to the public about alternative sports during the pandemic.